Biotechnological approaches to rose breeding - Marchant, Robert (1994)
The production of new rose cultivars by sexual crossing is problematic and time consuming due to sexual incompatibility. the failure of seeds to genninate. and to a limited gene pool. Biotechnology provides an obvious alternative for the creation of genetic novelty in rose. This thesis focuses on the development of novel approaches, based on embryo rescue, pollen cryopreservation, protoplast and transformation technologies. A reproducible embryo rescue technique was developed in which embryos were excised and genninated on agar solidified medium containing a basic salt mixture and carbohydrate. The choice of carbohydrate and the growth conditions employed were demonstrated to markedly affect the percentage germination and subsequent plantlet development. This technique was used to greatly increase the production of F, hybrid progeny when compared to conventional germination methods. The failure of sexual crosses between several English rose cultivars was shown to be due to a combination of low pollen viability and to the operation of a pollen-style incompatibility mechanism (probably of the gametophytic self-incompatibility type). Degree of flower opening and method of pollen dehiscence were shown to significantly affect pollen viability. A technique was developed for the effective cryopreservation of English rose pollen. Using this technique it was possible to store pollen at ultra-low temperatures without any significant loss in viability. Such a technique compared favourably with conventional techniques (refrigeration and freezing) in which a loss in viability over time was demonstrated to occur. In vitro shoot cultures of English rose were established on MS-based media containing BAP. GA3 and NAA following the treatment of explants with an antioxidant solution to negate the effects of phenolic oxidation. The production of callus was shown to be genotype dependant and lacked regeneration potential. Rhizogenic responses were observed in leaf discs of two cultivars however shoot regeneration was not observed. Using a variety of enzyme mixtures it was possible to isolate protoplasts from both In vitro leaf material and from cell suspensions. Both mesophyll and cell suspension derived protoplasts were cultured to a microcallus stage. Plating density, growth regulator concentration and the use of antioxidants were all demonstrated to have a significant effect on the protoplast plating efficiency. Rhizogenesis was achieved from mesophyll protoplast-derived calli. Protoplasts, sometimes labelled with a fluorescent marker, were subjected to both chemical and electrofusion. Using micromanipulation, heterokaryons, formed during electrofusion, were recovered. Such heterokaryons, when cultured. underwent division and formed microcalli which subsequently developed into calli. The hybrid nature of such calli were conftrmed by isozyme analysis, determination of ploidy level and RAPD analysis. The introduction of a plasmid containing a gus marker gene into zygotic embryos of English rose was shown to be possible. This was achieved by microprojectile-mediated DNA delivery using a laboratory built electrical discharge device. The efficiency of this technique was influenced by the concentration of microprojectiles and DNA used. And by firing distance and choice of DNA construct. The relevance of this study and its applications, in the context of rose breeding are discussed.